Physiological Correlates of Cycling Performance in Amateur Mountain Bikers (Baltic Journal of Sport and Health Sciences, 2012)
Research background and hypothesis. Aerobic fitness of high-performance mountain bikers explains about 40% of variance in performance. This suggests that other factors such as anaerobic power and capacity as well as technical abilities need to be considered in the physiological assessment (Impellizzeri et al., 2005 a). We found a lot studies investigating track and road cyclists, but there are no studies concerning the relationship between physiological tests and cycling performance in Lithuanian mountain bikers. The aim of this study was to investigate the physiological correlates of cycling performance in amateur mountain bikers. Research  methods.  Fifteen  Lithuanian  mountain  bikers  participated  in  the  study.  The  10-second  test  was performed to estimate special alactic anaerobic power output, whereas ae 30-second Wingate test was performed to estimate composite alactic anaerobic glycolytic power output. For the evaluation of the aerobic capacity, a progressive incremental laboratory cycling test to exhaustion was performed. Research results. We found a significant negative correlation between cycling performance and alactic anaerobic relative  peak  power  output  (r  =  –0.534,  p  0.05). Discussion and conclusions. Our findings suggest that alactic anaerobic power output and active glycolysis play a very important role in off-road cycling performance. This is essential because of the fast starting phase of the race and steep climbs.Keywords: mountain bike, cycling, performance, power output, maximal oxygen uptake.